Efficacy of cognitive-behavioral therapies in the treatment of post-traumatic stress disorder: A literature review (Research, Society and Development, 2024)
Post-Traumatic Stress Disorder (PTSD) is a severe psychiatric condition that can develop after exposure to traumatic events such as violence, natural disasters, or severe accidents. Cognitive-Behavioral Therapies (CBT) have been extensively studied and recommended as a first-line treatment for PTSD due to their proven efficacy in symptom reduction. This literature review aims to examine the efficacy of CBT in treating PTSD, focusing on specific modalities such as Prolonged Exposure Therapy (PE), Cognitive Therapy (CT), and Cognitive Processing Therapy (CPT). PE involves gradual and controlled exposure to traumatic stimuli, while CT focuses on cognitive restructuring to alter dysfunctional beliefs related to the trauma. CPT combines elements of exposure and cognitive restructuring, helping patients process traumatic memories and modify negative thoughts. Recent studies indicate that these approaches are effective in reducing PTSD symptoms such as re-experiencing, avoidance, and hypervigilance, and in improving patients' quality of life. However, efficacy may vary depending on individual factors such as trauma severity and comorbidities, and contextual factors such as the treatment environment. These findings highlight the need for personalized treatment and further research to optimize interventions and ensure they are accessible and effective for diverse populations.